Management Strategy of Fishery Port Samudera Kutaraja - Safiatuddin, Lia; Novianti, Rinda; Malta, Malta (PT. Hafasy Dwi Nawasena, 2024)
This research aims to analyze the condition and function of the facilities and operational activities of PPS Kutaraja for investment in the marine and fisheries sector, measure the performance and factors that support the performance of PPS Kutaraja and formulate a management strategy for PPS Kutaraja facilities. The research was carried out at the Kutaraja Ocean Fisheries Port (PPS), Kuta Alam District, Banda Aceh City, Aceh Province, which took place from June to August 2022. The editor has the right to edit the abstract for reasons of clarity of the abstract conThis research uses descriptive research methods with a quantitative approach. The research parameters are conditions and facilities, factors that support performance and strategies for improving facility management at the Kutaraja Ocean Fisheries Port (PPS). The research results show that the condition of the basic, functional and supporting facilities at the Kutaraja Ocean Fisheries Port (PPS) are all in good condition. performance and factors that support performance at the Kutaraja Ocean Fisheries Port (PPS) consist of the amount of fish production, frequency of ship visits, distribution of clean water, ice and fuel. Strategy for Improving Management of Kutaraja Ocean Fishery Port (PPS) Facilities based on the results of the SWOT analysis and determining the grand strategy is in Quadrant I with the SO strategy matrix. This strategy is applied based on a very favorable situation with the opportunities and strengths it has so that it can take advantage of existing opportunitiestent.